2011
DOI: 10.5694/j.1326-5377.2011.tb04139.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reacting antibodies against the pandemic (H1N1) 2009 influenza virus in older Australians

Abstract: Objective: To assess background pre‐pandemic cross‐reacting antibodies to the pandemic (H1N1) 2009 virus in older populations in Australia. Design, setting and participants: Data were opportunistically generated from three cross‐sectional pre‐pandemic studies involving people aged 60 years or older: a 3‐year (2006–2008) study of influenza outbreaks in aged care facilities (ACFs) in Sydney; an investigation of a respiratory virus outbreak in an ACF in rural New South Wales in June 2009; and a non‐influenza sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…High sequence similarity (∼80%) was found between the two pandemic viruses (1918 and 2009), with the differences restricted mainly to the Ca region of HA. This agrees with the findings of Booy et al (2009), Morens et al (2010), and Hancock et al (2009) that cross-reactive antibodies to H1N1pdm do exist in older people.…”
Section: Genetic Mutationssupporting
confidence: 92%
“…High sequence similarity (∼80%) was found between the two pandemic viruses (1918 and 2009), with the differences restricted mainly to the Ca region of HA. This agrees with the findings of Booy et al (2009), Morens et al (2010), and Hancock et al (2009) that cross-reactive antibodies to H1N1pdm do exist in older people.…”
Section: Genetic Mutationssupporting
confidence: 92%
“…Conversely, cross-reactive total antibodies were present at somewhat higher titers among female than male mice. In humans, women reportedly have a higher frequency of cross-reacting antibodies against pandemic 2009 H1N1 than men, as measured by hemagglutination inhibition [67]. Although hemagglutination inhibition titers correlate well with virus neutralizing titers [68], the strain specificity of the virus neutralization assay may have reduced detection of cross-reacting antibodies against HA in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…In New Zealand, 22.6% (95% CI: 15.3–30%) of adults >60 years old (N = 124 samples) had pre-existing protection (determined by HI assay) [29]. In North Queensland, Australia, 19% (95% CI: 4–34%) of adults >65 years old (n = 27) had pre-existing immunity (determined by HI assay) while a larger study of 259 adults >60 years old in Australia found pre-existing immunity in 37.5% (95% CI: 31.6–43.3%) [33], [34]. In the United States, 34% of adults born before 1950 (N = 115) had cross-reactive antibodies to pH1N1 (determined by MN) [9] while in Hong Kong 37% (n = 30) adults >65 years showed seroprotective levels of antibodies to pH1N1 [35].…”
Section: Discussionmentioning
confidence: 96%